2021
DOI: 10.1080/2162402x.2021.1940676
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor efficacy of a combination therapy with PD-L1 targeted alpha therapy and adoptive cell transfer of PD-1 deficient melanoma-specific human T-lymphocytes

Abstract: The optimization of adoptive transfer approaches of anti-tumor T cells requires both the functional improvement of the injected T cells and the modulation of the tumor microenvironment, favoring the recruitment of these T cells and their activation. We have recently shown the therapeutic benefit of two approaches tested individually in a melanoma model wich were on one hand the adoptive transfer of specific T cells deficient for the expression of the inhibitory receptor PD-1, and on the other hand PD-L1 target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Another study utilized HER-2+ transgenic mice models to study the ef of CAR-T cells with and without PD-1 inhibition, and it was observed that the comb tion therapy improved the therapeutic efficacy of CAR-T-cells against solid cancers [ The synergy seen in the combination therapy is likely multifactorial, being a produ increased T-cell effector activity and other effects, such as enhanced T-cell survival [1 Investigations into the gene editing of CAR-T cells have revealed that PD1-knoc CAR-T cells are a clinically efficacious alternative to combination therapy. Specifical was observed in murine models that editing the PD1 gene on tumor-specific T-cel reduce the expression of PD-1 resulted in a significant delay in tumor growth follow administration to PD-L1 overexpressing tumors [107,108]. Further data supports t findings, in that PD-1 deficient CAR-T cells showed significantly better antitumor effi than wild-type CAR-T cells [109][110][111].…”
Section: Adoptive Cellular Therapymentioning
confidence: 69%
See 1 more Smart Citation
“…Another study utilized HER-2+ transgenic mice models to study the ef of CAR-T cells with and without PD-1 inhibition, and it was observed that the comb tion therapy improved the therapeutic efficacy of CAR-T-cells against solid cancers [ The synergy seen in the combination therapy is likely multifactorial, being a produ increased T-cell effector activity and other effects, such as enhanced T-cell survival [1 Investigations into the gene editing of CAR-T cells have revealed that PD1-knoc CAR-T cells are a clinically efficacious alternative to combination therapy. Specifical was observed in murine models that editing the PD1 gene on tumor-specific T-cel reduce the expression of PD-1 resulted in a significant delay in tumor growth follow administration to PD-L1 overexpressing tumors [107,108]. Further data supports t findings, in that PD-1 deficient CAR-T cells showed significantly better antitumor effi than wild-type CAR-T cells [109][110][111].…”
Section: Adoptive Cellular Therapymentioning
confidence: 69%
“…Investigations into the gene editing of CAR-T cells have revealed that PD1-knockout CAR-T cells are a clinically efficacious alternative to combination therapy. Specifically, it was observed in murine models that editing the PD1 gene on tumor-specific T-cells to reduce the expression of PD-1 resulted in a significant delay in tumor growth following administration to PD-L1 overexpressing tumors [107,108]. Further data supports these findings, in that PD-1 deficient CAR-T cells showed significantly better antitumor efficacy than wild-type CAR-T cells [109][110][111].…”
Section: Adoptive Cellular Therapymentioning
confidence: 84%
“…The optimization of adoptive transfer of anti-tumor T cells requires both the functional improvement of the injected T cells and the modulation of the tumor microenvironment, favoring the recruitment of these T cells and their activation. Marotte et al [13] have investigated and demonstrated the safety and the superiority of a combination between the adoptive transfer of PD-1 de cient T cells and targeted alpha therapy (TAT) PD-L1 to control the growth of melanoma tumors in NSG mice (NOD scid gamma mouse, i.e., immunode cient laboratory mice). Thus, they provide the rst proof-of-concept of the e cacy of a combination therapy using TAT, adoptive cell transfer and genomic editing of IC-coding genes.…”
Section: Adverse Eventsmentioning
confidence: 99%
“…ACT is an important method for immune cell therapy of infiltrative tumors, using the antitumor characteristics of lymphocytes to remove primary and metastatic tumor cells [ 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 ]. Autologous (patient’s own) or allogeneic (donor’s) tumor-infiltrating lymphocytes (TILs) are activated in vitro, expanded to a certain number, and reinfused into the patient [ 118 , 119 , 120 , 121 ].…”
Section: The Emerging Of Cancer Immunotherapymentioning
confidence: 99%